Determinants of MSME performance: Assessing the role of budgeting, financial control, and cash management in Banjarbaru City - Nirwana, Ros; Jakiroh, Jakiroh; Bintari, Endah Sri; Anizar, Sri Yunia; Yulia, Yulia (Privietlab, 2025)
Many MSMEs play an important role in supporting local economic activity; however, yet in reality many of them still struggle with financial management issues that prevent their performance from reaching its full potential. Based on this situation, the present study examines how budgeting practices, financial control, and cash management influence the performance of MSMEs in Banjarbaru City. The analysis draws on the Resource-Based View (RBV), Contingency Theory, and Working Capital Theory as the main theoretical foundations. This study uses a quantitative associative approach and involves 30 business owners selected through purposive sampling method. The collected data were processed using multiple linear regression with SPSS 25. The results indicate that budgeting (β = 0.295; p = 0.037), financial control (β = 0.400; p = 0.002), and cash management (β = 0.481; p = 0.002) have a positive and significant effect on MSME performance, both partially and simultaneously (F = 79.389; p = 0.000). The adjusted R² of 0.890 indicates that these financial management variables can account for approximately 89% of the variation in MSME performance, which shows how strongly they are tied to day-to-day business outcomes. The results suggest that financial managerial skills function as important internal resources, as described in the RBV perspective, while the effectiveness of financial practices still depends on how well they fit each business’s specific situation, in line with Contingency Theory. The findings also reaffirm the idea from Working Capital Theory that maintaining adequate liquidity is essential for keeping operations running smoothly. Overall, this study offers empirical evidence from a growing city context and underlines the need for more structured budgeting, tighter financial control, and better cash management to support stronger and more sustainable MSME.